Environmental, social and governance, corporate social responsibility, and stock returns: What are the short‐ and long‐Run relationships?. (4th July 2022) - Feng, Gen‐Fu; Long, Han; Wang, Hai‐Jie; Chang, Chun‐Ping
Abstract: What are the relationships between corporate environmental, social, and governance (ESG), corporate social responsibility (CSR), and stock returns? Existing research has affirmed the impact of ESG or CSR on stock returns, but the discussion on the cointegration relationship among these three variables is still insufficient. Therefore, we use panel data of ESG ratings, CSR scores, and annual stock returns of 684 Chinese‐listed companies from 2011 to 2020 to verify the relationship between the variables through panel CADF and Westerlund tests. Meanwhile, we use PMG estimation to find that, in the long run, CSR significantly promotes the improvement of corporate stock returns, but ESG hurts the stock returns of most corporates. Further research proves that the impact of ESG on stock returns closely relates to corporate profitability. Our findings provide valuable policy implications for both developing and semi‐efficient market countries to help them improve their ESG and CSR performance.